US domestic sentiment reactions to climate and economic policy uncertainties: a quantile ARDL approach - Walid M. A. Ahmed; Mohamed A. E. Sleem (Journal of Applied Economics)
Over the years, climate and economic policy uncertainties have become critical considerations that shape public attitudes. They have the potential to impact people’s perceptions of financial stability, ecosystem integrity, and environmental sustainability. This paper aims to provide evidence on the sensitivity of US business and consumer sentiments to uncertainties arising from climate and economic policies in both short-term and long-term perspectives, and across different sentiment states. Our empirical investigation draws on a quantile ARDL approach, after orthogonalizing original sentiment series with respect to a diverse range of influential factors. The results reveal that climate and economic policy-related uncertainties have a negative impact on business (consumer) sentiment in the short and long run (only in the short run). These effects are particularly more pronounced when pessimistic sentiment begins to take hold. Moreover, we find evidence of locational asymmetry, especially in the long run.